1981
DOI: 10.1172/jci110075
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary gonadotropin-releasing hormone receptors. Effects of castration, steroid replacement, and the role of gonadotropin-releasing hormone in modulating receptors in the rat.

Abstract: A B S T R A C T To study the role of gonadotropin-releasing hormone (GnRH)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
48
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(51 citation statements)
references
References 43 publications
3
48
0
Order By: Relevance
“…Although it is well known that gonadal steroid hormones regulate the serum levels and pituitary content of LH (6)(7)(8)(9)(10)(11)(12)(13), little is known about their regulation of the biosynthesis of the subunits of LH at the transcriptional and the posttranscriptional levels. The excess production of a-subunits over LHf-subunits (14,15) has suggested that the rate of LHfl-subunit synthesis determines the amount of intact LH produced (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Although it is well known that gonadal steroid hormones regulate the serum levels and pituitary content of LH (6)(7)(8)(9)(10)(11)(12)(13), little is known about their regulation of the biosynthesis of the subunits of LH at the transcriptional and the posttranscriptional levels. The excess production of a-subunits over LHf-subunits (14,15) has suggested that the rate of LHfl-subunit synthesis determines the amount of intact LH produced (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Gonadectomy in rats is invariably associated with a 2-3-fold rise in gonadotrophin-releasing hormone receptors coincident with the rise in serum gonadotrophins (Frager, Pieper, Tonetta, Duncan & Marshall, 1981 ;Clayton & Catt, 1981a;Conne, Scaglioni, Lang, Sizonenko & Aubert, 1982). These responses can be prevented by immunoneutralization with a specific GnRH antiserum (Frager et ai, 1981; Clayton, Popkin & Fraser, 1982) suggesting that increased endogenous GnRH is essential for the post-gonadectomy rise in pituitary GnRH receptors and serum gonadotrophins.…”
Section: Introductionmentioning
confidence: 99%
“…GnRH acts by an initial step of binding to a plasma membrane receptor (28,29), and a considerable body of evidence has shown that GnRH is the main regulator of its own receptor on the gonadotroph. Castration results in an increase in GnRH receptors (GnRH-R), and this effect can be abolished by hypothalamic lesions, administration of GnRH anti-sera, or replacement of testosterone (30)(31)(32)(33). These manipulations prevent the rise in GnRH after castration, and injections of GnRH given subcutaneously every 8 h increased GnRH-R in these animals (30,32).…”
Section: Introductionmentioning
confidence: 99%
“…Castration results in an increase in GnRH receptors (GnRH-R), and this effect can be abolished by hypothalamic lesions, administration of GnRH anti-sera, or replacement of testosterone (30)(31)(32)(33). These manipulations prevent the rise in GnRH after castration, and injections of GnRH given subcutaneously every 8 h increased GnRH-R in these animals (30,32). Low dose infusions of GnRH can also increase GnRH-R, whereas high dose infusions reduce receptor number (34).…”
Section: Introductionmentioning
confidence: 99%